2020
DOI: 10.3390/nu12092699
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Anti-Inflammatory Effects and Related Mechanisms of Processed Egg Yolk, a Potential Anti-Inflammaging Dietary Supplement

Abstract: Egg-yolk based supplements have demonstrated biological effects. We have developed a novel processed egg-yolk (PEY) complement, and we have tested whether it has inflammation modulatory properties. These were evaluated in a lipopolysaccharide (LPS)-challenge in 1-month male rats by in vivo circulating cytokine profiles measured by multiplexing techniques. Cell culture was used to explore ex vivo properties of derived serum samples. We explored growth factor composition, and mass-spectrometry metabolome and lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…administered Wistar rats in vivo were treated with PEY and commercial egg yolk (2000 mg/kg) to two different groups, and the serum levels of cytokines including IL-1β, TNF-α, and MCP-1, were evaluated in both groups. The authors indicated that PEY group showed a significant reduction in concentrations of IL-1 β, TNF-α, and MCP-1 when compared with the commercial egg yolk group, and concluded that the complex biomolecules present in PEY might effectively control the chronic inflammation and aging and help reduce the inflammaging progression [156].…”
Section: Egg Yolkmentioning
confidence: 99%
“…administered Wistar rats in vivo were treated with PEY and commercial egg yolk (2000 mg/kg) to two different groups, and the serum levels of cytokines including IL-1β, TNF-α, and MCP-1, were evaluated in both groups. The authors indicated that PEY group showed a significant reduction in concentrations of IL-1 β, TNF-α, and MCP-1 when compared with the commercial egg yolk group, and concluded that the complex biomolecules present in PEY might effectively control the chronic inflammation and aging and help reduce the inflammaging progression [156].…”
Section: Egg Yolkmentioning
confidence: 99%
“…PEY consists of an egg preparation obtained through a patented process from the fertilized egg-yolk [5]. A potent anti-inflammatory effect of PEY treatment has been recently reported in vivo [6]. Among the multitude of PEY components, highlight the presence of growth factors such as connective tissue growth factor (CTGF), platelet-derived growth factor (PDGF), and insulin-like growth factor (IGF-1) [6]; all of them with proven beneficial effects in the growth of hair follicles [7,8] Also, PEY exhibits a differential lipidomic and metabolomic profile with lipids clustered among different sphingolipid-related and immune-related pathways, and metabolites present in pathways related to omega-3 fatty acids, among others [6].…”
Section: Introductionmentioning
confidence: 99%